Development of Language Materials for National Development: A language Management Perspective - Maroko, Geoffrey Mokua (International Journal of Education and Research, 2013)
Learning resources need to be revised periodically to reflect the changing socio-cultural, economic, political and technological realities in the society. The current Primary English Syllabus was revised in 2002. Yet, publishers are developing materials for teaching English language in primary schools using 2002 syllabus as their reference. The question that arises is: to what extent are these materials aligned to the new realities in Kenya? As a response to these questions, this paper identifies the themes and language norms addressed in the Primary English Syllabus (2002) and selected language-learning materials. Next, it analyses cases in language materials in use which are not in line with the themes and norms presented in the syllabus. The paper shows that some content in the learning materials are inconsistent with the norms while emerging topical issues are lacking. To address these concerns, the paper recommends the language management in any future materials evaluation efforts.
Full text available online at http://ir-library.ku.ac.ke/bitstream/handle/123456789/8827/Development%20of%20language%20materials....pdf?sequence=3&isAllowed=y
Keywords: Materials; evaluation; development; language management; themes; norms